Ablation of experimental colon cancer by intratumoral 224Radium-loaded wires is mediated by alpha particles released from atoms which spread in the tumor and can be augmented by chemotherapy. (February 2015) - Reitkopf-Brodutch, Shira; Confino, Hila; Schmidt, Michael; Cooks, Tomer; Efrati, Margalit; Arazi, Lior; Rath-Wolfson, Lea; Marshak, Gideon; Kelson, Itzhak; Keisari, Yona
Abstract: Purpose: We developed 224 Ra-loaded wires, which release by recoil alpha emitting nuclei into solid tumors and cause tumor cell killing. This research examined if the major damage was inflicted by alpha particles emitted from these atoms or by direct gamma and beta emissions from the inserted wires. We also examined the efficacy of this treatment against colon cancer in combination with chemotherapy. Materials and methods : Mouse colon carcinomas (CT-26 xenografts), treated by intra-tumoral radioactive wires loaded with 224 Ra atoms were monitored for effects on tumor growth, intratumoral tissue damage and distribution of alpha emitting atoms. The effects were compared with those of 224 Ra-loaded wires coated with poly methyl methacrylate (PMMA), which blocks atom recoil. Similar experiments were performed with radioactive wires combined with systemic 5-FU. Results : 224 Ra-loaded wires inhibited tumor growth and formed necrotic areas inside the tumor. PMMA coated wires did not inhibit tumor growth, and caused minor intratumoral damage. Autoradiography images of tumors treated with 224 Ra-loaded wires revealed a spread of alpha emitters over several mm, whereas PMMA-coated wires showed no such spread. Injection of 5-FU with 224 Ra-loaded wires augmented tumor growth retardation and cure. Conclusions : 224 Ra-loaded wires ablate solid tumors by the release of alpha-particle emitting atoms inside the tissue, an effect that can be enhanced by combining this method with chemotherapy.